Modeling Feedback in Interaction With Conversational Agents—A Review - Axelsson, Agnes; Buschmeier, Hendrik; Skantze, Gabriel (Frontiers in Computer Science, 2022)
Intelligent agents interacting with humans through conversation (such as a robot, embodied conversational agent, or chatbot) need to receive feedback from the human to make sure that its communicative acts have the intended consequences. At the same time, the human interacting with the agent will also seek feedback, in order to ensure that her communicative acts have the intended consequences. In this review article, we give an overview of past and current research on how intelligent agents should be able to both give meaningful feedback towards humans, as well as understanding feedback given by the users. The review covers feedback across different modalities (e.g., speech, head gestures, gaze, and facial expression), different forms of feedback (e.g., backchannels, clarification requests), and models for allowing the agent to assess the user's level of understanding and adapt its behaviour accordingly. Finally, we analyse some shortcomings of current approaches to modelling feedback, and identify important directions for future research.